Young Steinbeck Boy - unknown:::Creator::::::::::::
Thom Steinbeck or possibly John Steinbeck IV sitting, fishing off of a dock. An inscription on back reads: 'Hasn't caught one yet that he didn't feel so sorry for that he threw it back in....'